القيادة الإدارية وعلاقتها بمهارات الإدارة الإلكترونية - ريغي, بوخالفة (كلية العلوم الانسانية والاجتماعية جامعة محمد بوضياف المسيلة, 2022)
تناولت الدراسة موضوع القيادة الإدارية وعلاقتها بمهارات الإدارة الإلكترونية وقد تمحورت مشكلة البحث حول هل توجد علاقة بين القيادة الإدارية و مهارات الإدارة الإلكترونية في كلية العلوم الانسانية والاجتماعية بجامعة المسيلة؟ وقد وظفت هذه الدراسة المنهج الوصفي التي يتيح للباحث جمع أكبر عدد ممكن من الحقائق والمعلومات ووصفها وتحليلها أما أدواته فقد تمثلت في الملاحظة والإستبيان بالإضافة إلى أسلوبي التحليل الكيفي والكمي وقد تمثل مجتمع الدراسة في موظفي كلية العلوم الانسانية والاجتماعية حيث استخدمنا الحصر بالعينة وبلغ عددهم 35 موظف. Abstract: The study dealt with the subject of administrative leadership and its relationship to electronic management skills. The research problem revolved around the question: Is there a relationship between administrative leadership and electronic management skills at the Faculty of Humanities and Social Sciences at the University of M'sila? This study has employed the descriptive approach, which allows the researcher to collect, describe and analyze the largest possible number of facts and information. As for its tools, it was represented in the observation and the questionnaire, in addition to the qualitative and quantitative methods of analysis. The study community was represented by the staff of the College of Humanities and Social Sciences, where we used a sample inventory of 35 employees..
Keywords: القيادة - القيادة الإدارية - الإدارة - الإدارة الإلكترونية - كلية العلوم الانسانية و الاجتماعية .Leadership - Administrative leadership - Management - Electronic management - College of Humanities and Social Sciences